Can antler stage represent an activity driver in axis deer Axis axis?. Issue 1 (19th April 2019) - Kavčić, Krešimir; Safner, Toni; Rezić, Andrea; Ugarković, Damir; Konjević, Dean; Oršanić, Milan; Šprem, Nikica
Abstract : The aim of this study was to determine the seasonal activity patterns and asynchrony between different antler stages in male axis deer from the Mediterranean island of Rab in Croatia using camera traps. Nine cameras with an infrared motion detection system were used to track animal activity over a 12‐month period, 24 h per day. Stags were divided into two categories of antler development: regeneration stage and hard antler stage. The frequency of detection of each category in the photographs allowed us to investigate seasonal activity patterns. To describe the seasonal activity pattern in each category, we fitted the segmented linear regression and predicted that the ratio of monthly activity of stags in the two antler categories would interchange regularly during the research period. Over the 12‐month study period, 36 862 photographs were analysed. A significant difference in frequency was found between the two antler categories (p < 0.01), with a consistently greater presence of hard‐antlered stags. The highest frequency of detection of both antler categories was found in the winter season, and the lowest in spring. The segmented linear regression clearly distinguished three break points in April, June and December in the hard antler stage, with a significant difference in activity pattern among the months for each slope. On the other hand, no significant difference was found for the regeneration stage. Therefore, the expected proportional interchange in the number of stags in the two antler stages throughout the year did not occur. This study revealed that the Mediterranean axis deer population showed a unique activity pattern, where antler stage may act as a possible driver regulating stag movements.